Line of sight how improved information, transparency, and accountability would promote the adequate resourcing of health facilities across Papua New Guinea.
It explores information gaps and transparency issues that undermine health service delivery and outcomes. Recommendations in this report aim to improve health sector governance and capacity, which will ultimately contribute to a more robust and equitable health care system.